Pre-Service Teachers’ Perspectives on the Implementation of Song-Based Instruction in Teaching English to Early Childhood Learners - Danti Pudjiati; Andi Musda Mappapoleonro; Hisham Abd. Malik; Nur Fitria, Tira (Universitas Nahdatul Ulama Surabaya, 2024)
This study describes perceptions from pre-service teachers regarding the use of songs in teaching English to young children. The research method comprised qualitative methods. The research subjects consisted of 69 students of early childhood education programs at a private university. The findings explore four primary themes of the students, namely (1) the pedagogical value attributed to songs, (2) the attitudes of students towards the use of songs, (3) the opinions of students concerning the songs utilized, and (4) the perceived effectiveness of songs. The findings indicate a consensus among the respondents on the efficacy of using songs as a tool to introduce English to young children. The investigation into pre-service teachers' perspectives on song-based instruction in teaching English to early childhood learners reveals several key insights. First, pre-service teachers strongly support the inclusion of English songs in the curriculum, recognizing their pedagogical value in enhancing linguistic proficiency and engaging young learners. They agree that songs make learning enjoyable and improve auditory skills, aligning with existing literature on the benefits of song-based education. Second, despite concerns about resource availability and selecting appropriate songs, pre-service teachers believe that songs do not negatively impact learners' concentration or English proficiency assessments. They acknowledge challenges like potential disruptions and time constraints but see overall benefits. Third, teachers view songs as effective tools for vocabulary retention and promoting the automatic use of the target language. While they appreciate the engaging nature of songs, there is some disagreement about their effectiveness in reducing language acquisition anxiety. Fourth, pre-service teachers find English songs accessible and are positive about their use in the classroom, though opinions vary on the frequency of implementation, but most agree on the integration of songs into the curriculum.